India higher education report 2017 :Teaching,learning and quality in Higher education - Varghese, N. V.,Ed; Anupam Pachauri,Ed; Sayantan Mandal,Ed (Sage, 2018)
"Understanding teaching, learning and quality in higher education requires in-depth engagement with theoretical discourse and empirical evidences. With this objective, the Centre for Policy Research in Higher Education (CPRHE) has initiated multiple research activities to develop deeper insights into quality concerns in higher education. India Higher Education Report 2017 evaluates the Indian higher education system in terms of teaching, learning and quality and presents a comprehensive analysis of reforms that took place in these domains. Organized into three major parts--ranking, research and quality; teachers and teaching-learning; and quality management--this book discusses changes and issues that have affected the country's higher education system in recent times. This seminal work is a must-have for scholars and researchers of education, social science and public policy"--